THE ETHICS OF NATARIES IN SHARIA CONTRACTS - Ramadha Nul Karim (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Notary is an official in the legal field who has obligations or duties in the legal field, especially a type of legal consultation which is usually in the civil domain, such as relating to an agreement or something similar to people in need. Notaries also have the authority to provide or issue authentic deeds that have legal force both in terms of proof and legal certainty. Agreements that can use the services of a notary so that they have strong legal value are not only based on conventional contract models but also contracts or agreements that use sharia principles. A notary also has obligations and limitations regarding his authority based on the Notary Position Law and the Notary Code of Ethics. Regardless of the background of a notary, whether a Muslim or not, the notary is required to behave professionally, which means he is able to carry out his authority and duties in accordance with the legal corridors legalized for him. If a notary is faced with making a deed using a contract model that uses sharia principles, then from a legal point of view the only thing that can be used is sharia principles which are legal from the point of view of state law. Many types of contracts that have been legalized are stated in the policies or authority currently held by sharia financial institutions or similar because all types of deeds issued by them are also considered to be authentic Atta or deeds that can have legal value. Apart from the notary's attachment to the rules that legalize his authority in Islam, there are 5 basic principles related to the professionalism of a legal profession, namely the principle of freedom, the principle of justice, the principle of honesty, the principle of free will, the principle of responsibility.